Comparison between Measured and Predicted Basal Metabolic Rate in Indonesian Adolescent Female Basketball Players - Mochammad Rizal; Nazhif Gifari; Ni Putu Dewi Arini (Amerta Nutrition)
Background: Accurate estimation of energy requirement is significantly crucial for athletes to support performance. Meanwhile, Basal Metabolic Rate (BMR) constitutes the largest component of Total Energy Expenditure (TEE) and is commonly assessed using estimation formulas.